Public access to building related energy data for better decision making in implementing energy effciency strategies:Legal barriers and technical challenges - Geissler, Susanne; Charalambides, Alexandros G.; Hanratty, Michael (My University, 2019)
The EU is committed to achieve ambitious energy effciency and CO2 reduction targets. Regarding improving the energy performance of the building stock, detailed building related energy data made accessible by means of GIS are crucial. For this purpose, geo-referenced data from Energy Performance Certificates (EPC) according to the Energy Performance of Buildings Directive is of central importance, in order to facilitate decision-making about large-scale renovation projects and developing targeted products and services. The ENERFUND project developed a method and subsequently an internet based tool making use of EPC data from 13 EU member states as well as other open-source data (such as renovation costs), thus clearly demonstrating the feasibility and usefulness of this approach. However, also technical challenges and legal barriers were encountered, such as a lack of data and varying data specifications depending on the national transposition of the European Directive, and different interpretation of specific clauses of the General Data Protection Regulation depending on EU member states' societal norms. Recommendations include the development of guidance notes to be issued by the responsible EU bodies to specify and harmonize data for mandatory public access, to ensure the effective implementation of energy effciency and CO2 reduction policies in the EU's building sector.
Keywords: Enerfund; Energy effciency of building stock; Energy performance certificate; Energy performance of buildings directive (epbd); General data protection regulation (gdpr); Geodata; Personal data; Renovation strategy